2015
DOI: 10.1586/14737159.2015.1063420
|View full text |Cite
|
Sign up to set email alerts
|

Current and future molecular diagnostics in non-small-cell lung cancer

Abstract: The molecular investigation of lung cancer has opened up an advanced area for the diagnosis and therapeutic management of lung cancer patients. Gene alterations in cancer initiation and progression provide not only information on molecular changes in lung cancer but also opportunities in advanced therapeutic regime by personalized targeted therapy. EGFR mutations and ALK rearrangement are important predictive biomarkers for the efficiency of tyrosine kinase inhibitor treatment in lung cancer patients. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 144 publications
(127 reference statements)
0
9
0
Order By: Relevance
“…Harmonization is a long-term process that is ideally evidence-based yet also innovative, facilitates close interactions between the laboratory and clinician, and is a shared responsibility for all stakeholders (63). Industry involvement could help to establish pilot projects between healthcare institutions and insurers, and provide financial support through which to assess proposed diagnostic approaches for routine use, with a view to better understanding issues such as indications, tissue requirements, turnaround times, reliability, pitfalls, and costs (59,61,64,65).…”
Section: Challenge 4: Harmonization Of Diagnostics Involves Several Dmentioning
confidence: 99%
“…Harmonization is a long-term process that is ideally evidence-based yet also innovative, facilitates close interactions between the laboratory and clinician, and is a shared responsibility for all stakeholders (63). Industry involvement could help to establish pilot projects between healthcare institutions and insurers, and provide financial support through which to assess proposed diagnostic approaches for routine use, with a view to better understanding issues such as indications, tissue requirements, turnaround times, reliability, pitfalls, and costs (59,61,64,65).…”
Section: Challenge 4: Harmonization Of Diagnostics Involves Several Dmentioning
confidence: 99%
“…Advances in genomic technology, such as NGS, have expanded the breadth and depth of the detection of gene alterations and have made it possible to analyze broad molecular profiling simultaneously, for discovering the comprehensive functional therapeutic targets in lung cancers [138][139][140]. The implementation of NGS permits the output of sequences with megabases to gigabases of genetic information in a single run using a limited amount of input DNA; this has enabled a shift in detection from single genes towards multigene panels [141].…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…In recent years, the main treatments for advanced NSCLC have been chemotherapy, molecular-targeted therapy and developing immunotherapy (6)(7)(8). Although molecular targeted therapies have resulted important changes in the treatment of NSCLC, especially for adenocarcinoma, the odds of patients with lung cancer surviving for at least 5 years after diagnosis remain <15% (9). The pathogenesis behind lung cancer has not been fully elucidated, and research has shown that factors such as polygenes may be involved.…”
Section: Introductionmentioning
confidence: 99%